Eccentric Capitellar Ossification Limits the Utility of the Radiocapitellar Line in Young Children. Issue 2 (March 2016) - Fader, Lauren M.; Laor, Tal; Eismann, Emily A.; Cornwall, Roger; Little, Kevin J.
Abstract : Background: The radiocapitellar line (RCL) has long been used for the radiographic evaluation of elbow alignment. In children, the capitellar ossific nucleus serves as a proxy for the entire capitellum, but this substitution has not been verified. Using magnetic resonance imaging (MRI), we sought to understand how maturation of the ossific nucleus of the capitellum affects the utility of RCL throughout skeletal maturation of the elbow. Methods: The RCL was drawn on coronal and sagittal MRIs in 82 children (43 boys, 39 girls; age range, 1 to 13 y) with at least 3 patients in each 1-year interval age group. The perpendicular distance of the RCL from the center of both the cartilaginous capitellum and the capitellar ossific nucleus was measured relative to its total width, and a percent offset for each measurement was calculated. Logarithmic regression analysis was performed to analyze the effect of age and sex on percent offset. Results: The RCL reliably intersected with the central third of the cartilaginous capitellum at all ages in both planes. Although the RCL intersected with the ossified capitellum in all but 3 measurements, it intersected with the central third of the ossified capitellum less often in younger children in both sagittal ( B =0.47, P <0.001) and coronal ( B =0.31, P =0.002) planes. Percent offset decreased significantly with age in a logarithmic manner in both sagittal ( r =0.57, P <0.001) and coronal ( r =−0.47, P <0.001) planes. 95% confidence intervals predict that the sagittal plane RCL will accurately intersect the central third of the ossified capitellum by age 10 years in girls and age 11 years in boys but not in the coronal plane. Conclusions: Eccentric ossification of the capitellum explains RCL variability in young children. The RCL does not reliably intersect the central third of the ossified capitellum until ages 10 years in girls and 11 years in boys in the sagittal plane. The RCL should be used within its limitations in skeletally immature children and should be combined with advanced imaging if necessary. Level of Evidence: Level III—Prognostic.